Fraseologiens plass i ordbøker for innvandrere - Jónsson, Jón Hilmar (LexicoNordica, 1999)
Dictionaries for foreign speakers must differentiate between examples and collocations, on the other hand, and idioms, on the other hand. The Swedish Lexin dictionaries show the difference between these two types by different section marks, as well as making idioms into independent items in the text, accompanied by explanations. The topic of this paper is how idioms are treated in the Lexin dictionaries, their classification, and their link to the headwords, in light of the prospective user’s background and needs. It is maintained that the idioms should be chosen and ordered by their meaning, making them accessible to the users by the use of terms for selected concepts uniting semantically related idioms. The importance of semantic classification of this type is considered both in the light of Swedish and Icelandic data.